Evaluation of Cronobacter sakazakii inactivation and physicochemical property changes of non-fat dry milk powder by cold atmospheric plasma. (30th August 2019) - Chen, Dongjie; Peng, Peng; Zhou, Nan; Cheng, Yanling; Min, Min; Ma, Yiwei; Mao, Qingqing; Chen, Paul; Chen, Chi; Ruan, Roger
Highlights: This cold plasma system can facilitate high Cronobacter sakazakii inactivation. No obvious physiochemical changes in non-fat dry milk after cold plasma treatments. The adoption of proper gas mixture can minimize adverse effects on NFDM properties. Abstract: Cronobacter sakazakii can cause life-threatening infections in neonates. Exposure to contaminated powdered food, especially milk powder, is a major route for C. sakazakii infection. Cold atmospheric plasma (CAP) is well known as a non-thermal method for inactivating microbial pathogens. This study evaluates the effectiveness of CAP on C. sakazakii in non-fat dry milk (NFDM) powder using a fluidized reaction system. The CAP treatments for 20–120 s led to 1.17–3.27 log10 reductions of C. sakazakii . C. sakazakii inactivation increased with increasing flow rate from 8 to 20 L/min. In terms of quality attributes of NFDM after the CAP treatments, no noticeable color changes (ΔE < 1.5) were observed. Moreover, no significant changes in crystallinity, amino acid composition, or phenolic content occurred following a 120s-CAP treatment. These results indicate that this fluidized reaction system combined with CAP can provide an effective antimicrobial activity with minimal effects on some physicochemical properties of NFDM powder.